In vitro Analysis of the Intradiscal Pressure of the Thoracic Spine - Wilke, Hans-Joachim; Herkommer, Andrea; Werner, Karin; Liebsch, Christian (Frontiers in Bioengineering and Biotechnology, 2020)
The hydrostatic pressure of the nucleus pulposus represents an important parameter in the characterization of spinal biomechanics, affecting the segmental stability as well as the stress distribution across the anulus fibrosus and the endplates. For the development of experimental setups and the validation of numerical models of the spine, intradiscal pressure (IDP) values under defined boundary conditions are therefore essential. Due to the lack of data regarding the thoracic spine, the purpose of this in vitro study was to quantify the IDP of human thoracic spinal motion segments under pure moment loading. 30 fresh-frozen functional spinal units from 19 donors, aged between 43 and 75 years, including all segmental levels from T1-T2 to T11-T12, were loaded up to 7.5 Nm in flexion/extension, lateral bending, and axial rotation. During loading, the IDP was measured using a flexible sensor tube, which was inserted into the nucleus pulposus under x-ray control. Pressure values were evaluated from third full loading cycles at 0.0, 2.5, 5.0, and 7.5 Nm in each motion direction. Highest IDP increase was found in flexion, being significantly (p < 0.05) increased compared to extension IDP. Median pressure values were lowest in lateral bending while exhibiting a large variation range. Flexion IDP was significantly increased in the upper compared to the mid- and lower thoracic spine, whereas extension IDP was significantly higher in the lower compared to the upper thoracic spine, both showing significant (p < 0.01) linear correlation with the segmental level at 7.5 Nm (flexion: r = -0.629, extension: r = 0.500). No significant effects of sex or age were detected, however trends towards higher IDP in specimens from female donors and decreasing IDP with increasing age, potentially caused by fibrotic degenerative changes in the nucleus pulposus tissue. Sagittal and transversal cuttings after testing revealed possible relationships between nucleus pulposus quality and pressure moment characteristics, overall leading to low or negative intrinsic IDP and non-linear pressure-moment behavior in case of fibrotic tissue alterations. In conclusion, this study provides insights into thoracic spinal IDP and offers a large dataset for the validation of numerical models of the thoracic spine.